New Common Evaluation Framework for IMF Capacity Development. (Policy Papers; Policy Paper, 2017)
new common evaluation framework for the Fund's capacity development (CD) activities. The new common evaluation framework is intended to streamline current practices and increase comparability and use of results by adopting for all CD evaluations a common four-step process that includes use of the OECD Development Assistance Committee (DAC) evaluation criteria. Around this common approach, there is flexibility to adapt evaluations to reflect the wide range of CD activities. Key elements of the framework are grouped around the objectives of: producing shorter, more focused, and more comparable evaluations; improving the information supporting evaluations;spending the same level of resources on evaluations while allocating these scarce resources more efficiently; and using the information from evaluations to alter practices or shift the targeting of CD resources.